PENERAPAN PENDEKATAN BRAIN BASED LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI KELAS IX SMP NEGERI 1 LABUHAN DELI - Khairani Khairani; Juhairiah Juhairiah; Marojanah Panjaitan (Universitas Islam Nusantara, 2018)
This study is a classroom action research that aims to find out whether the students 'learning motivation in grade IX SMPNegeri 1 Labuhan Deli can be improved by applying mathematics learning with Brain Based Learning approach andknowing how the students' learning result with the application of Brain Based Learning approach. The research instrumentused to measure students' motivation in the form of questionnaires while the instrument to measure student learning outcomesin the form of tests. Based on the result of questionnaire of initial motivation given to the students before the action, it isknown that the low motivation level of the students with the average of the initial motivation questionnaire score is 44.21and the percentage of grade motivation level is 55.26%. After giving action on cycle I, the mean of student motivationquestionnaire score is 47,97 and the percentage of class motivation level is 59,97%. Next on the second cycle, the averagestudent motivation questionnaire score is 53 and the percentage of grade motivation level of 66.25%. From the results oftests given to students it is known that the number of students who completed in the first cycle of 61.54% while in the secondcycle 87.18%, obtained student learning completeness level in classical increased by 25.64%. Thus, the application of BrainBased Learning approach to mathematics learning at SMP Negeri 1 Labuhan Deli can improve students' motivation andlearning outcomes.